MANAGEMENT OF GESTASIONAL DIABETES MELLITUS IN A BETA MAJOR THALASSEMIA PATIENT - Troy Fonda; Hermina Novida (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Gestational diabetes mellitus (GDM) is a hyperglycemic condition that is first discovered during pregnancy. GDM is a high-risk condition during pregnancy, for both mother and fetus. GDM affects about 1–14% of pregnancies. In the last 20 years, the incidence of gestational diabetes has been increasing. High iron load and disorders of iron metabolism have been associated with glucose metabolism. The beta thalassemias are a group of hereditary hemoglobinopathies. Treatment for beta thalassemias patients is transfusion, but intensive transfusion can aggravate iron overload in patients. In this study, a case of GDM in a pregnant woman with beta-thalassemia was reported.